Higher-Order Thinking Skills Profile of Islamic Boarding School Students on Geometry through the STEM–based Video Approach - Pujiastuti, Heni; Haryadi, Rudi (International Journal of STEM Education for Sustainability, 2023)
The Indonesia government has begun to focus and pay attention to the quality of education in Islamic Boarding School. Education is a provision for the future to create quality human resources. Education is strongly linked to the 21st century, where education has rapidly developed in science and technology to generate worldwide competitiveness. Students' higher-order thinking skills are fundamental, where this thinking ability is an ability to understand and find solutions to problems in varied and different ways. An appropriate learning approach must support Higher-order thinking skills. Higher-order thinking skills are intelligence with specific knowledge that leads to reasoning, analytical skills, problem-solving, and critical and creative thinking skills. Higher-order thinking skills are the major objective of educational institutions in implementing education that uses a quasi-experiment. Participants consisted of Islamic Boarding School students, ten male- and ten female students. A STEM-based video is a learning approach that can help students analyze, solve problems, investigate a phenomenon, create skills in students, and produce higher-order thinking skills. This study's STEM-based Video approach process is designed to solve functional mathematics problems in real life concerning geometry.